High intensity ultrasonication of fermentative Jun tea: Evaluation of physicochemical, microbiological and rheological properties - Subhashree Aparimita; Sourav Misra; Chirasmita Panigrahi; Shubham Mandliya; Hari Niwas Mishra (Food Physics, 2025)
Jun tea, a non-alcoholic functional drink, can confer physiological and neurological benefits to human beings. Various phenolic components in Jun tea are degraded in an acidic condition by the enzymatic activity of bacteria and yeast present in the tea fungal association. Therefore, this study aimed to explore the efficacy of ultrasonication (750 W power; 27 kHz frequency) on the physicochemical, microbiological and rheological properties of Jun tea with variation in treatment time (20–40 min). The total phenolic content (TPC), antioxidant activity, pH, and cloud stability of Jun tea were significantly (p < 0.05) increased after the ultrasonic treatment, which was further confirmed by the FTIR spectra analysis. In contrast, prolonged exposure to ultrasound resulted in a significant declination of alcohol content, whiteness index, plate count, and apparent viscosity of Jun tea. The outcomes of this study explore the application of low-cost non-thermal technology (ultrasound technique) in fermented beverage industries. This product replaces the extensive use of commercially available carbonated beverages.